The Right to Nondiscrimination and Universality in Public Policies for Overcoming Extreme Poverty in Chile. Subsystem Securities and Opportunities and Chile Solidario - Contreras Álvarez, Jaime (2016)
This research aims to analyze the presence of a right based approach in public policy for overcoming poverty in Chile, specifically the components of Nondiscrimination and Universality in the Social Protection subsystems “Chile Solidario” and replacement of this, called “Seguridades y Oportunidades”, released as “IngresoÉtico Familiar”. To reach this objective a qualitative research type was developed, using data collection mechanisms interviews with key actors (designers and implementers) and document analysis and then triangulate the obtained information. The results show a lack of universality in the access as a result of targeting mechanisms and annual quotas by province, women empowerment in the group home, but also gender discrimination and inequality in the distribution of roles and tasks within the homes. It is recommended to eliminate the annual quota systems by province, to remove the rigidities intervention methodologies for the correct application of the rights perspective in public policies, especially considering right holders in extreme poverty.